2007
DOI: 10.1002/elps.200700013
|View full text |Cite
|
Sign up to set email alerts
|

Transport of charged samples in fluidic channels with large zeta potentials

Abstract: In this article, we present an analysis on the transport of charged samples through micro- and nanofluidic channels with large zeta potentials (|zeta| > (kBT)/e). Using the Method of Moments formulation, the diffusion-convection equation has been solved to evaluate the mean velocity and the dispersion of analyte bands in a parallel-plate device under electrokinetically- and pressure-driven flow conditions. The effect of electromigration induced by the lateral electric field within the Debye layer has been quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 27 publications
1
13
0
Order By: Relevance
“…As a consequence of the transverse ion distributions produced by the electric fields inside EDLs, the mean ion speed (zone velocity) $\bar{u}_{i}$ in nanofluidics becomes dependent on the ion charge z i and is given by 7–18 where $\bar{u}_{{i{\rm {p}}}}$ and $\bar{u}_{{i{\rm {e}}}}$ denote, respectively, the mean ion speed due to pressure‐driven fluid flow and electroosmotic fluid flow, $\langle \cdots \rangle = (n + 1)\mathop{\int}_0^a {( \cdots )(y/a)^{n} {\rm {d}}(y/a)}$ signifies the cross‐sectional area‐average ( n =0 or 1) and B i =exp(− z i Ψ) characterizes the Boltzmann distribution of ions in the transverse direction. In nanochannel electrophoresis, no pressure gradient is applied so that $\bar{u}_{{i{\rm {p}}}} = 0$ .…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…As a consequence of the transverse ion distributions produced by the electric fields inside EDLs, the mean ion speed (zone velocity) $\bar{u}_{i}$ in nanofluidics becomes dependent on the ion charge z i and is given by 7–18 where $\bar{u}_{{i{\rm {p}}}}$ and $\bar{u}_{{i{\rm {e}}}}$ denote, respectively, the mean ion speed due to pressure‐driven fluid flow and electroosmotic fluid flow, $\langle \cdots \rangle = (n + 1)\mathop{\int}_0^a {( \cdots )(y/a)^{n} {\rm {d}}(y/a)}$ signifies the cross‐sectional area‐average ( n =0 or 1) and B i =exp(− z i Ψ) characterizes the Boltzmann distribution of ions in the transverse direction. In nanochannel electrophoresis, no pressure gradient is applied so that $\bar{u}_{{i{\rm {p}}}} = 0$ .…”
Section: Theorymentioning
confidence: 99%
“…fluid flow in nanochannels, which has been growing exponentially over the past decade 1–5. In nanoscale channels where the hydraulic diameter is comparable to the electrical double layer (EDL) thickness, the enormous electric fields inside EDL produce transverse ion distributions that depend on the ion charge 6–10. As a consequence, the non‐uniform fluid flow along nanochannels, which may be electric field‐driven 11, 12 or pressure‐driven 11–14, yields charge‐dependent mean ion speeds enabling the separation of ions by charge alone.…”
Section: Introductionmentioning
confidence: 99%
“…3 will likely be reduced by a factor on the order of two. Similar considerations arise for electroosmomotic flow [14,15,37], and as such the results in Fig. 3 should be viewed as qualitative in nature and representing an upper bound on the attainable resolution.…”
Section: Local Optimization For a Single Speciesmentioning
confidence: 71%
“…Since these early studies, theoretical and numerical investigations have explored in more detail various aspects of this new technique, including dispersion [11][12][13], impact of the z potential [14], channel geometry [15], hindered diffusion [16] and nonlinear field affects due to the finite size of macromolecules [17]. Despite this continued interest, however, only a few studies [16][17][18][19] have reported the capabilities of the process, as measured by peak resolution, and only a handful have addressed the factors that determine this.…”
Section: Introductionmentioning
confidence: 99%
“…Without using the Boltzmann equation, Qu et al [34] derived new governing equations for the overlapped EDL fields, its results showed that the modified model predicts a lower electric potential in the EDL field than the classical theory. Using the different models, Dutta [35,36] presented the electroosmotic transport through rectangular channels with small and large zeta potentials by Taylor-Aris dispersivity, respectively. The results showed that if zeta potential was large enough that there were overlapped EDL fields, the mean velocity and the slug dispersivity can vary as much as an order of magnitude comparing with small zeta potential.…”
Section:  mentioning
confidence: 99%